Avaliação da sazonalidade nas características sexuais de touros bubalinos (Bubalus bubalis) criados em clima subtropical úmido (19º latitude sul) - Guilherme de Oliveira Andrade (2016)
Buffalo (Bubalus bubalis) is considered a seasonally polyestrous species with an improved efficiency on reproduction when the daylight decreases. While in females this subject is already well known, in male the studies are conflicting and the majority were done on North Hemisphere. In this thesis, the season influence on reproductive characteristics of male Murrah buffaloes raised in a humid subtropical region at latitude 19º 37 12 south and longitude 44º 02 38 west was evaluated. In this regard, the year were divided into bimesters and semen was collected once a week using an artificial vagina. The physical and morphological characteristics of the semen were evaluated and the reaction time and sexual behavior observed were noted. Significant differences in vigor and sperm morphology among months were found. Therefore, it was concluded that buffaloes raised in the latitude of this experiment were not influenced by seasonality considering the reproductive characteristics evaluated.